PERSONAL QUALITIES OF A MODERN SCHOOL TEACHER THE QUESTION OF FORMATION IN THE PROCESS OF PROFESSIONAL TRAINING - Ismailova Dilbar Rozmatovna (Scholar Express Journal, 2022)
This article focuses on the issue of shaping the personal qualities of a modern school teacher in the process of professional training. This is one of the topical topics of today, where the psychological characteristics of a modern teacher, the basics of the formation of pedagogical abilities are studied
Keywords: Modern school teacher; ability; personal qualities